ANALISIS KESIAPAN PENERAPAN E-GOVERNMENT DALAM MENDUKUNG TATA KELOLA PEMERINTAHAN PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN JENEPONTO - Azwar Wijaya Syam; Irham Irham; Sudirman Sudirman (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Analysis of E-Government Implementation Readiness in Supporting Governance at the Department of Communication and Informatics of Jeneponto Regency, South Sulawesi Province. Based on the research problem, the objective of this study is to analyze the level of readiness for e-government implementation in supporting governance at the Department of Communication and Informatics of Jeneponto Regency, South Sulawesi Province. The research method used is a qualitative approach with a descriptive qualitative design to examine the readiness of e-government implementation at the Department of Communication and Informatics of Jeneponto Regency, South Sulawesi Province. The analytical method includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that the readiness for e-government implementation in supporting governance at the Department of Communication and Informatics of Jeneponto Regency, South Sulawesi Province, is categorized as fairly ready but not yet optimal. The main strengths include the use of core applications (SIMAKDA, SIPD, and SIMBADA) that are relatively user-friendly, the official portal that provides information transparency, and the provision of support and incentives for employees to improve their ICT skills. However, several challenges remain, including misaligned policies between central and regional levels, a shortage of IT personnel, network instability in certain areas, and inadequate data security systems. These conditions lead to issues such as delays in digital public services, low efficiency in data integration, cybersecurity risks, and difficulties in maintaining service sustainability. Therefore, to enable the Department of Communication and Informatics to achieve a more efficient, secure, and sustainable standard of digital governance, improvements in infrastructure, regulations, and human resource capacity are required.